NIACIN REQUIREMENT FOR SPORULATION OF PHYSARUM POLYCEPHALUM - Daniel, John W. (1962)
Daniel, John W. (University of Wisconsin, Madison, Wis.) and Harold P. Rusch. Niacin requirement for sporulation of Physarum polycephalum. J. Bacteriol. 83:1244–1250. 1962.—The myxomycete Physarum polycephalum undergoes sexual sporulation if exposed to light after 4 days of incubation in the dark on a salts medium containing niacin, niacinamide, or tryptophan. None of these compounds is required for growth. Quinic acid, shikimic acid, intermediates of the kynurenine pathway, diphosphopyridine nucleotide (DPN), and triphosphopyridine nucleotide (TPN) replace niacin but a number of other tryptophan metabolites do not. Analogues of niacin inhibit sporulation when added at the beginning but not at the end of dark incubation with niacin. Folic acid, p-aminobenzoic acid, and p-aminobenzenesulfonamide inhibit sporulation if added at any time during the incubation or illumination periods. Reduced di- or triphosphopyridine nucleotide, but not DPN or TPN, reverse the p-aminobenzoic acid inhibition but do not replace the light requirement or shorten the dark incubation period. Gluconate and 2-ketogluconate also replace niacin. Glucose, pyruvate, malate, and oxalacetate inhibit the niacin-induced sporulation. Iodoacetate and fluoride do not counteract the glucose effect or inhibit sporulation.